2002
DOI: 10.1055/s-2002-33876
|View full text |Cite
|
Sign up to set email alerts
|

Severe Intestinal Bleeding caused by Intestinal Metastases of a Primary Angiosarcoma of the Thyroid Gland

Abstract: A 75 year old male presented with gastrointestinal bleeding after resection of both upper lobes of the lungs because of metastases. One year ago an angiosarcoma was the reason for a complete removal of the thyroid gland. In esophago-gastro-duodenoscopy we found multiple hemorrhagically stained polyploids lesions in the postbulbar duodenum and jejunum. Colonoscopy showed isolated polyploid lesions of the right flexura. Because of persistent gastrointestinal bleeding a diagnostic laparotomy was done. Intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…However, there are considerable controversy about the true existence of thyroid angiosarcomas. Although it is histologically defined as cleft-like anastomosing spaces lined by large, atypical cells of endothelial lineage [7], some authors believe that most of the reported cases are anaplastic or undifferentiated carcinomas with angiomatoid features [3, 4]. Many authors believe that thyroid angiosarcoma is a variant of sarcomatoid carcinoma, in view of their nearly constant cytokeratin positivity in the neoplastic elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are considerable controversy about the true existence of thyroid angiosarcomas. Although it is histologically defined as cleft-like anastomosing spaces lined by large, atypical cells of endothelial lineage [7], some authors believe that most of the reported cases are anaplastic or undifferentiated carcinomas with angiomatoid features [3, 4]. Many authors believe that thyroid angiosarcoma is a variant of sarcomatoid carcinoma, in view of their nearly constant cytokeratin positivity in the neoplastic elements.…”
Section: Discussionmentioning
confidence: 99%
“…In Southern Italy, no case of thyroid angiosarcoma has been described. Thyroid angiosarcoma is also a very aggressive tumor that can rapidly spread to the cervical lymph nodes, lungs, and brain or can metastasize to the duodenum, small bowel, and large bowel and induce severe bleeding [1, 4–6]. …”
Section: Introductionmentioning
confidence: 99%
“…Tumors can also metastasize to the duodenum, small and large bowel and can cause severe bleeding [6]. In the present case, anemia and mild splenomegaly was determined pre- operatively.…”
Section: Discussionmentioning
confidence: 63%
“…Aggressive tumors can rapidly spread to the lungs, lymph nodes and the brain [1,[6][7][8]. Tumors can also metastasize to the duodenum, small and large bowel and can cause severe bleeding [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation